ANTARA TRADISI DAN REALITAS: STUDI TENTANG PREFERENSI TEMPAT TINGGAL PASCA NIKAH DI KALANGAN MASYARAKAT DONGGO (Perspektif Sosiologi Budaya dan Hukum Islam) - Habibi, Muhammad Margasastra; Amrulloh, Moh. Asyiq; Fik, Fikran; Fikran, Fikran (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines post-marital residential preferences among the Donggo community from the perspective of cultural sociology and Islamic law. The Matrilocal tradition that requires couples to live with the wife's family is still dominant, but has begun to shift along with increasing education, social mobility, and the influence of modernity. Islam, as the majority religion, provides a flexible normative basis, emphasizing the principles of justice, security, and comfort in determining a place of residence, without specifying a specific location. This study uses a qualitative approach with interview techniques, observation, in the Donggo community, Bima, NTB. The results of the study indicate a negotiation between customary values, aspirations of young couples, and sharia principles. Neolocal choices are increasingly developing among young couples as an expression of independence, although they are still faced with traditional social pressures. This phenomenon reflects complex social dynamics, where customary law and Islamic law interact adaptively in responding to changes in cultural values. Thus, post-marital residential preferences in the Donggo community illustrate shifts in social structure, cultural transformation, and the actualization of justice values ​​in the context of the Islamic family